From Heartland and Rimland, to Hyperland: Introducing a New Geopolitical Theory - Koukakis, Georgios (HAPSc Policy Briefs Series, 2024)
Despite the fact that many geopolitical theories have been conceived, the conditions of the contemporary geopolitical environment have changed dramatically, leading major actors to behaviours that cannot be easily explained such as the New Space Race, massive (dis)information campaigns/operations, and cyber operations. The purpose of this article is to introduce a new geopolitical theory that facilitates the interpretation of this behaviour in the context of the emerging dynamics of the geopolitical arena and identify the new strategic domains that contribute to the enhancement of a state’s national power.